2017
DOI: 10.3389/fnins.2017.00007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Systemic Metabolic Fuels on Glucose and Lactate Levels in the Brain Extracellular Compartment of the Mouse

Abstract: Classic neuroenergetic research has emphasized the role of glucose, its transport and its metabolism in sustaining normal neural function leading to the textbook statement that it is the necessary and sole metabolic fuel of the mammalian brain. New evidence, including the Astrocyte-to-Neuron Lactate Shuttle hypothesis, suggests that the brain can use other metabolic substrates. To further study that possibility, we examined the effect of intraperitoneally administered metabolic fuels (glucose, fructose, lactat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 168 publications
(187 reference statements)
2
24
0
Order By: Relevance
“…38,39 Astrocytes internalize lactate via MCT1/4 but the concentration of the blocker used in our study blocks only neuronal MCT2. 23,40 The concentration of glucose used was necessary to induce and maintain the epileptiform activity in slices due to the differences in metabolite diffusion in the in vitro brain slice preparation as compared to the intact brain. Of late, lactate is considered as a signaling molecule rather than the normally held view of its role as a metabolite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38,39 Astrocytes internalize lactate via MCT1/4 but the concentration of the blocker used in our study blocks only neuronal MCT2. 23,40 The concentration of glucose used was necessary to induce and maintain the epileptiform activity in slices due to the differences in metabolite diffusion in the in vitro brain slice preparation as compared to the intact brain. Of late, lactate is considered as a signaling molecule rather than the normally held view of its role as a metabolite.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the inhibitory effect of lactate is not due to the glucose concentration used in external solution, as studies have shown that systemic increase in glucose concentration does not lead to significant increase in lactate concentration in brain extracellular space. 23,40 The concentration of glucose used was necessary to induce and maintain the epileptiform activity in slices due to the differences in metabolite diffusion in the in vitro brain slice preparation as compared to the intact brain. 3,5-DHBA reduced the spike frequency; however, unlike lactate it did not result in hyperpolarization of subicular neurons, which can be due to various possibilities like the shift in membrane potential can be partially dependent on the intracellular cAMP level that is downregulated by lactate-HCA1-G i signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the balance between blood and brain cells may differ between the brain homogenates of control and mutant mice. As lactate concentrations in the blood are two- to three-fold higher than those in the mouse brain (extracellular compartment) ( Béland-Millar et al , 2017 ), such differences may represent an additional confounding factor. Although differences in genetic background are also of concern when making comparisons between different mouse strains ( Wolfer et al , 2002 ), we utilized over nine backcrossings in addition to littermates within each strain.…”
Section: Discussionmentioning
confidence: 99%
“…Peripherally produced insulin-like growth factor-1 crosses the blood–brain barrier and enhances the neuroprotective potential of astrocytes through binding to the receptors expressed on their cell membranes ( Ang et al, 1993 ; Gray et al, 2017 ). Lactate released by astrocytes is believed to be taken up and utilized as an energy source by neurons ( Béland-Millar et al, 2017 ). Other important functions of astrocytes include clearance of excess glutamate from the inter-synaptic space to prevent neuronal damage due to hyper-excitation ( Barres, 1991 ).…”
Section: Limitationsmentioning
confidence: 99%